Fast estimation of effective permeability and sweep efficiency of waterflooding in geologically heterogeneous reservoirs - Gago,PA; King,PR; Muggeridge,AH (2016)
Geological heterogeneity can adversely affect the macroscopic sweep efficiency when waterflooding oil reservoirs, however the exact distribution of permeability and porosity is generally not known. Engineers try to estimate the range of impacts heterogeneity might have on waterflood efficiency by creating multiple geological models and then simulating a waterflood through each of those realizations. Unfortunately each simulation can be computationally intensive meaning that it is generally not possible to obtain a statistically valid estimate of the expected sweep and the associated standard deviation. In this paper we show how the volume of unswept oil can be estimated rapidly (without flow simulations) from a geometrical characterization of the spatial permeability distribution. A "constriction" factor is defined which quantifies the effective cross-section area of the zones perpendicular to the principal flow direction. This is combined with a 'net-To-gross ratio' (which quantifies the fractional reservoir volume occupied by the zones that contribute to flow) to estimate effective permeability and the expected recovery factor for that realization. The method is tested using a range of realistic geological models, including SPE10 model 2 and its predictions are shown to agree well with values obtained using a well established commercial flow simulator.